Global Domination in Bipolar Fuzzy Graphs (Journal of Informatics and Mathematical Sciences, 2017)
In this paper the concept of global domination in bipolar fuzzy graph is introduced and studied its characterization. The necessary and sufficient condition for the global dominating set is given in terms of domination between the vertices. Also semi complete, purely semi complete, semi complementary and semi global domination concepts are defined and some results are obtained.
Keywords: Bipolar fuzzy graph (BFG); Strong edge; Dominating set; Domination number; Global dominating set; Global domination number; Semi complete; Purely semi complete; Semi complementary; Semi global dominating set and semi global domination number